Analisis Kepuasan Pengguna Aplikasi Mobile Banking Bca Menggunakan Metode System Usability Scale Pada Mahasiswa Universitas Dinamika Bangsa (UNAMA) Jambi - Zelvia Krisna Senjani; Dodo Zaenal Abidin; Nurhadi (LPPM Universitas Dinamika Bangsa, 2025)
This study analyzes the level of user satisfaction of BCA mobile banking application using System Usability Scale (SUS) method on students of UNAMA University Jambi. Based on PlayStore review data, BCA mobile application gets a rating of 3.9 out of 5. Some user complaints include application that often force close, difficulty finding transaction history, complex transfer process, and balance information that does not appear immediately. The results of the SUS test show variations in the level of user acceptance, with scores below 50 categorized as Not Acceptable, scores of 50-70 as Marginal, and scores above 70 as Acceptable. Partial statistical tests show that the variables Effectiveness (X1), Efficiency (X2), and Satisfaction (X3) significantly affect the Usability variable (Y). The simultaneous test produces an F value = 279.269 with a significance of 0.000 (<0.05), which indicates a significant relationship between X1, X2, and X3 to Y. The coefficient of determination (Adjusted R²) of 0.897 indicates that 89.7% of the Usability variable is influenced by Effectiveness, Efficiency, and Satisfaction, while the remaining 10.3% is influenced by other factors outside this study. This study concludes that although the level of user satisfaction is quite high, there are a number of aspects that need to be improved to improve the user experience of the BCA mobile banking application.